Shrimp (Peneaus Vannamei) pond sludge characteristics - Ling, Teck Yee; Lydia, K.P.S.; Lee, Nyanti (Proceeding of the 3rd Regional Conference on Natural Resources in the Tropics (NRTrop3), 2009)
Shrimp aquaculture is an important industry in Sarawak as it brings income and provides protein for the local population. However, during harvesting, sludge at the bottom of the pond had to be removed from the pond before the next stocking occurs. The characteristics of pond sludge had to be studied so that nutrients can be recycled. Therefore, the objective of this study was to determine the characteristics of shrimp pond sludge. Sludge from five ponds was analyzed for particle size, organic matter and total phosphorus. Results indicate that sediments from the five ponds were classified under silt and clay loam with 15-29% clay, 36-62% silt and 18-35% sand. pH ranged from 1.3-1.6g/cm3. Sludge was rich in organic matter ranging from 11-19%. As for total phosphorus, the values ranged from 203 to 294 ug/g. Zinc concentrations (9-21 mg/kg) was higher than copper (6-10 mg/kg). Regression indicated that total phosphorus is significantly correlated with clay content in the sludge with R2 of 87.3%. This shows the association of phosphorus with clay fraction in the sludge. This study shows that sludge contains macronutrient such as phosphorus and micronutrients such as Zn and Cu for plants and those nutrients need to be recycled to prevent water pollution and replenish the depleting non-renewable resource.